تأثير قاعدتي الاستحالة والاستهلاك في أحكام الأغذية والأدوية: دراسة فقهية تحليلية = The impact of the two maxims of istiḥālah and istihlāk upon the rulings on food and medicine: an analytical juristic study - Syed Yusuf, Sayed Muhammad Redzuan; Arif, Arif Ali; Zakariyah, Luqman (IIUM Press, International Islamic University Malaysia, 2018)
يهدف هذا البحث إلى دراسة تأثير قاعدتي الاستحالة والاستهلاك في أحكام الأغذية والأدوية، وذلك باتخاذ مادة الجلاتين والكحول أنموذجاً. وقد اعتمد الباحثون في هذه الدراسة على المنهج الاستقرائي؛ بهدف تتبع الفتاوى الصادرة حول المستجدات في الأغذية والأدوية المختلف في حرمتها والنظر فيها من وجهة نظر طبية وفقهية معاً للتكامل بينهما، كما استخدم الباحثون المنهج التحليلي في بيان أسباب اختلاف الفقهاء في أنواع المحرمات في مستجدات الغذاء والدواء، وتحليلها، والوقوف على ذلك، مع بيان الضوابط التي تتفق مع مقاصد الشريعة والقواعد الفقهية. وانتهت الدراسة إلى نتائج أهمها: إن قاعدتي الاستحالة والاستهلاك لا تتحققان عند تصنيع الجلاتين لعدم تغرير الذات البروتيني للأجزاء الخنزيرية وعظامها، إضافة إلى أن تصنيعه لا يُعد تغريراً طبيعياً. كما أن الكحول تختلف عن الخمور؛ لأنه قد يوجد في بعض المواد الغذائية بطبيعته، وأنَّ الخمور مشر وب مسكر، فحرام تناوله سواء أكان قليلاً أم كثيراً. ويرى الباحثون أنَّ ما رر جح وه، يجوز الخروج عليه في حالة الضرورة؛ بناءً على القاعدة الفقهية: "الضرورات تبيح المحظورات". ******************************************************** This study focuses on the Islamic rulings regarding food and medicine from the perspective of two maxims, istiḥālah and istihlāk, with gelatine and alcohol as the case studies. The researchers applied the inductive method for examining fatāwā issued on new and latest food and medicine whose forbiddance is disputed and for investigating them from both perspectives of medicine and Islamic jurisprudence in order to make integration between them. Likewise, the researchers used the analytical approach in clarifying the reasons for variation between the scholars of Islamic jurisprudence regarding the types of prohibited substances in the latest food and medicine, while analysing and pondering upon them, and clarifying the regulations that confirm the objectives of the Sharī‘ah and maxims of Islamic jurisprudence. This study concludes with these findings: the maxims of istiḥālah and istihlāk are not achieved in the production of gelatin. As for alcohol, it is not the same as intoxicants, therefore their consumption is prohibited in both little amounts and large amounts. The researchers opine that the rulings they preferred may be overridden in cases of dire need based on the maxim of Islamic Jurisprudence: “dire need makes the prohibited permissible.”